Risk factors for transient tachypnea of newborns in the NICU room at Sylvani Hospital, Pahlawan Village, North Binjai District, Binjai City in 2024 - Damanik, Nopalina Suyanti; Simanjuntak, Parningotan; Manurung, Herna Rinayanti; Sinaga, Ribur; Ginting, Astaria Br; Syahputri, Asry Febrina (Institute of Computer Science (IOCS), 2024)
According to WHO estimates, there were 5 million neonatal deaths and 4.5 million infant deaths worldwide in 2020, with 7.5% of these deaths occurring in the first year of life (Novitasari et al, 2020). The global incidence of LBW is 15.5% with a range of 10-50%. Since 2012, there has been a decrease in the number of newborns with low birth weight (LBW) by 29% to 30%, and efforts have been made to reduce the number of LBW babies by 30% by 2025. These statistics are supported by a decrease in LBW from 20 million to 14 million in 2012 to 2019 (Rizka P, 2021). Respiratory distress in newborns, or known as Respiratory Distress in Newborn (RDN), is often characterized by symptoms of tachypnea, namely a respiratory rate of more than 60 times per minute, accompanied by grunting, chest retraction, breathing through the nostrils, and cyanosis. Research conducted by Tochie, Choukem, Langmia, Barla, & Ndombo (2016) in Cameroon showed that RDN is a common emergency condition and has a high prevalence of morbidity and mortality. This statement is based on research findings from Nardello et al. (2017) and Babaei, Dehghan, & Pirkashani (2018), which showed that the most common cause of death in newborns was RDN, with a percentage of 72.2% of 79 babies born. Research Objective Risk Factors of Transient Tachypnea of ​​Newborn in NICU Room at Sylvani Hospital, Pahlawan Village, North Binjai District, Binjai City in 202. Research Method Retrospective survey using Cross Sectional approach. In this study using extensive dataset to see many cases and relationships between variables. The results of statistical analysis using Chi-Square test showed p value (Sign) = 0.001 (p <α = 0.05), there is a significant relationship between maternal age and the risk of Transient Tachypnea of ​​Newborn. significant relationship between KEK nutritional status and Transient Tachypnea of ​​Newborn Chi-Square showed p value (Sig) = 0.027 (p <α = 0.05).